A Rare 46,X,t(Y;10)(q12;p14) Balanced Translocation in Non-Obstructive Azoospermic Patient with Elevated FSH and LH Levels - Kousar Jahan Syeeda Khursheed; Mohammed Rahman Kaleemullah; Annu Joseph; Mohammed Hasan Al Durazi; Moiz Bakhiet (Case Reports in Genetics)
Structural chromosomal aberrations like translocations have been shown to cause spermatogenic failure. We report a rare 46,X,t(Y;10)(q12;p14) balanced translocation in an otherwise healthy non-obstructive azoospermic male with high follicle-stimulating hormone (26.65 IU/L) and high luteinizing hormone (13.58 IU/L). The patient was referred to us after clinical, hormonal, and histopathological investigations to identify chromosomal abnormalities by karyotyping and fluorescence in situ hybridization (FISH). Analysis of the banding pattern by karyotyping followed by FISH confirmed reciprocal translocation and identified the breakpoints at Yq heterochromatin (Yq12) and 10p14. Further molecular tests including AZF microdeletion assay were done, and the results, which showed no mutations in the analyzed genes, were provided by the referring doctor. Thus, our study points to the importance of conventional cytogenetic techniques in the preliminary evaluation of a genetic abnormality in cases of infertility and would help the patient make an informed decision before pursuing assisted reproductive technology.